Is further screening of men with baseline PSA < 1 ng ml−1 worthwhile? The discussion continues—Results of the Swiss ERSPC (Aarau). Issue 3 (23rd January 2015) - Randazzo, Marco; Beatrice, Josef; Huber, Andreas; Grobholz, Rainer; Manka, Lukas; Chun, Felix K.; Kluth, Luis A.; Wyler, Stephen F.; Recker, Franz; Kwiatkowski, Maciej
<x xml:space="preserve">Abstract</x> Recent studies indicate frequent early PSA retesting unrelated of men's baseline PSA, which increases the harms of early detection especially among men with low PSA. The current study investigates the PCa incidence among men with baseline PSA <1.0 ng ml−1 in order to adjust retest intervals for more targeted early detection. Between 1998 and 2012, 2, 416 men with baseline PSA <1.0 ng ml−1 were prospectively observed. Primary endpoint was PCa diagnosis. Negative predictive value (NPV) and number needed to screen (NNS) to detect one PCa were calculated. During a median follow‐up time of 12.1 years, 54 (2.2%) PCa were diagnosed with n = 26 (48.1%) among men with baseline PSA of 0.75 ≤ 1.0 ng ml−1 (upper baseline PSA quartile). The 10‐year probability of being diagnosed with PCa increased significantly from 0.19% (baseline PSA < 0.40 ng ml−1) to 2.0% (baseline PSA 0.40 ≤ 0.56 ng ml−1), 2.5% (baseline PSA 0.56 ≤ 0.75 ng ml−1) over 4.4% (baseline PSA 0.75 ≤ 1.0 ng ml−1) (all p values <0.0001), respectively. The frequency of Gleason ≥7 PCa increased from 1 (0.17%) to 8 (1.4%), 5 (0.8) over 11 (1.8%) in these groups. The 8‐year NPV for Gleason ≥ 7 PCa were 99.8 (baseline PSA < 0.40 ng ml−1), 99.8 (baseline PSA 0.40 ≤ 0.56 ng ml−1), 100 (baseline PSA 0.56 ≤ 0.75 ng ml−1) and 99.5 (baseline PSA 0.75 ≤ 1.0 ng ml−1), respectively. During 12 years, the numbers were 99.8, 98.6, 99.2, and 98.2, respectively. Therefore, due to the very low rate of Gleason ≥ 7 PCa, further screening might be omitted in men with baseline PSA < 0.4 ng ml−1. Between 0.4 and 1.0 ng ml−1, an 8‐year interval can be discussed.